Large-eddy simulation of pollutant dispersion from an area source over random height buildings arrays - Lavor, Vitor Ferreira (2019)
Large-eddy simulation (LES) is used to study the turbulent flow and the pollutant dispersion over urban-like arrays, where an area source was placed on the ground. Three different geometries are considered: two staggered building arrays, one with uniform building height and another with non-uniform building heights, and an aligned array with random height buildings. The spatial and temporal average of the streamwise velocity and time-averaged concentration are compared with measurements from a wind tunnel experiment in order to assess the accuracy of the results (CHENG; CASTRO, 2002a; PASCHEKE; BARLOW; ROBINS, 2008). These comparisons indicate that LES is adequate to capture the turbulent flow and the pollutant dispersion over the assessed configurations. The results obtained in the present study show that the height variability of the buildings is an important parameter to study the flow and dispersion phenomena in urban areas. Besides the building height variability, local geometrical features proved to be relevant to determine the dispersion behaviour such as the presence of a taller building upwind the approaching flow. It is shown that the turbulent motions are responsible for the vertical turbulent flux of pollutant leaving/entering the urban canopy. The intensity of the turbulent structures seems to be related to the building height variation, since the higher the building height, the greater is the layer in which the flow has larger vertical velocity fluctuations. Results also show that the vertical scalar flux close to the area source can affect downwind clean zones. The vertical advective scalar flux was found to have an effect on dispersion in the vicinity of the building (a local effect), while the vertical turbulent fluxes are associated with pollutant transportation downwind above the smaller buildings (a non-local effect)